2014
DOI: 10.1086/678419
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Patient Hand Hygiene in Multiorgan Transplant Units Using a Novel Technology: An Observational Study

Abstract: Patients appear to perform hand hygiene infrequently, which may contribute to transmission of pathogens from the hospital environment via indirect contact or fecal-oral routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 8 publications
1
5
1
2
Order By: Relevance
“…In this study, 75.8% of the participants washed their hands after using the toilet/bedpan/commode, but only 11.0% of them washed their hands before drinking fluids. Similar results have been observed in other study on patients in transplant units 20. Hospital environments are often contaminated with hospital-acquired pathogens,16–18 therefore, there is a need for education campaigns aimed at patient-initiated HH and HH, that is, directly observed before meals and the intake of medications during hospitalisation 21 22…”
Section: Discussionsupporting
confidence: 81%
“…In this study, 75.8% of the participants washed their hands after using the toilet/bedpan/commode, but only 11.0% of them washed their hands before drinking fluids. Similar results have been observed in other study on patients in transplant units 20. Hospital environments are often contaminated with hospital-acquired pathogens,16–18 therefore, there is a need for education campaigns aimed at patient-initiated HH and HH, that is, directly observed before meals and the intake of medications during hospitalisation 21 22…”
Section: Discussionsupporting
confidence: 81%
“…16 Prior to implementing the PHH bundle, we found that overall patient compliance with HH was only 13% and although more likely to occur after using the toilet, less than 5% of patients performed HH before eating. This was considerably lower than that suggested in a recent study by Srigley et al 27 where compliance was 30% after using the bathroom and 39% at mealtimes, although in this study the use of an electronic monitoring may over-estimate hand hygiene among a more mobile patient population. PHH prior to eating is particularly important given the risk of transferring pathogens acquired though touching the environment or staff onto mucous membranes or their ingesting when handling and consuming food in a hospital ward.…”
Section: Discussioncontrasting
confidence: 86%
“…Key model parameter estimates are shown in Table 1 . 6 , 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ,…”
Section: Methodsunclassified